Human Bone Marrow Adipose Tissue is a Metabolically Active and Insulin-Sensitive Distinct Fat Depot - Tam T. Pham; Kaisa K. Ivaska; Jarna C. Hannukainen; Kirsi A. Virtanen; Martin E. Lidell; Sven Enerbäck; Keijo Mäkelä; Riitta Parkkola; Sauli Piirola; Vesa Oikonen; Pirjo Nuutila; Riku Kiviranta (United States, 2022)
Context
Bone marrow (BM) in adult long bones is rich in adipose tissue, but the functions of BM adipocytes are largely unknown. We set out to elucidate the metabolic and molecular characteristics of BM adipose tissue (BMAT) in humans.
Objective
Our aim was to determine if BMAT is an insulin-sensitive tissue, and whether the insulin sensitivity is altered in obesity or type 2 diabetes (T2DM).
Design
This was a cross-sectional and longitudinal study.
Setting
The study was conducted in a clinical research center.
Patients or Other Participants
Bone marrow adipose tissue glucose uptake (GU) was assessed in 23 morbidly obese subjects (9 with T2DM) and 9 healthy controls with normal body weight. In addition, GU was assessed in another 11 controls during cold exposure. Bone marrow adipose tissue samples for molecular analyses were collected from non-DM patients undergoing knee arthroplasty.
Intervention(s)
Obese subjects were assessed before and 6 months after bariatric surgery and controls at 1 time point.
Main Outcome Measure
We used positron emission tomography imaging with 2-[18F]fluoro-2-deoxy-D-glucose tracer to characterize GU in femoral and vertebral BMAT. Bone marrow adipose tissue molecular profile was assessed using quantitative RT-PCR.
Results
Insulin enhances GU in human BMAT. Femoral BMAT insulin sensitivity was impaired in obese patients with T2DM compared to controls, but it improved after bariatric surgery. Furthermore, gene expression analysis revealed that BMAT was distinct from brown and white adipose tissue.
Conclusions
Bone marrow adipose tissue is a metabolically active, insulin-sensitive and molecularly distinct fat depot that may play a role in whole body energy metabolism.